2016
DOI: 10.1136/bcr-2016-218143
|View full text |Cite
|
Sign up to set email alerts
|

Incidental finding of giant pericardial lipoma

Abstract: We describe a patient with an incidental finding of a large mass adjacent to the heart detected on a screening CT scan. The differential diagnosis included primary and secondary tumours of the heart. Subsequent investigation with trans-thoracic echocardiogram and cardiac MRI confirmed a diagnosis of a giant pericardial lipoma, one of the common benign primary cardiac tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…However, there are a limited number of case reports of a large pericardial lipoma treated with a conservative approach. Salim et al [ 22 ] reported an asymptomatic patient with a large pericardial lipoma (12×5 cm) diagnosed by MRI. Based on the clinical and radiological characteristics, the patient qualified for conservative treatment with imaging follow-up; however, data on the follow-up were not provided.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a limited number of case reports of a large pericardial lipoma treated with a conservative approach. Salim et al [ 22 ] reported an asymptomatic patient with a large pericardial lipoma (12×5 cm) diagnosed by MRI. Based on the clinical and radiological characteristics, the patient qualified for conservative treatment with imaging follow-up; however, data on the follow-up were not provided.…”
Section: Discussionmentioning
confidence: 99%
“…La caracterización de los lipomas mediante TAC permite mostrar su contenido a través de la visualización de densidad grasa y sus relaciones anatómicas (figuras 4 y 5). Al respecto, el informe de los valores promedio de atenuación de las masas es inconstante a través de los estudios y se han descrito masas de baja densidad con atenuación entre 0 y -160 Unidades Hounsfield (17,43). Se documentan masas homogéneas que infrecuentemente tienen calcificaciones (11,46).…”
Section: Tomografía Axial Computarizadaunclassified
“…La mayoría de las descripciones de los reportes de caso se limitan a estas secuencias. Sin embargo, otros autores enfatizan la importancia de la caída de la señal de la grasa en secuencias con saturación como un hallazgo necesario para su confirmación (11,13,27,43,51).…”
Section: Resonancia Magnéticaunclassified
See 1 more Smart Citation